Application of Ultra-capacitor and Battery Hybrid Power Systemfor Diesel Locomotive Power Supply - Wu Hongjun; Chen Cheng; Huang Jingyun (机车电传动)
Operation goal and the structure of ultra-capacitor and battery hybrid power system for diesel locomotive power supplywas introduced, and the circuit design principle was expounded. Power capacity distribution ratio of the ultra-capacitor and battery wasresearched with experiment. The existing locomotive on-board operation validated the broad application prospects of hybrid power systemfor diesel locomotive power supply.